Systematic review and meta-analysis of colistin heteroresistance in Klebsiella pneumoniae isolates - Saeed Khoshnood; Mohammad Hossein Haddadi; Nourkhoda Sadeghifard; Abbas Maleki; Ebrahim Kouhsari; Hassan Valadbeigi (BMC Infectious Diseases, 2025)
Abstract Background Antibiotic heteroresistance is a common phenotype observed in a variety of pathogenic bacteria such as K. pneumonia: A subpopulation of cells with a higher MIC than the dominant population is defined as heteroresistance. Several studies have demonstrated colistin heteroresistance in K. pneumonia leading to treatment failures. Therefore, we performed a systematic meta-analysis to summarize the current evidence on the prevalence of colistin heteroresistance in K. pneumonia isolates. Methods Multiple databases were searched to find relevant literature from 2008 to 2024, including PubMed, Scopus, Embase, and Web of Science. Results The meta-analysis included eighteen articles. According to the random effects model, the pooled proportion of heteroresistant K. pneumoniae was 0.315 (95% CI: 0.179–0.492). The heterogeneity was substantial, with Q [17] = 335.020, I² = 94.93%, and p < 0.001, suggesting that heteroresistance rates varied widely across the 18 included studies. Conclusion In conclusion, our findings revealed that a prevalence of colistin heteroresistant detected in approximately 31.5%, of K. pneumonia. These findings are obtained and highlighted in this meta-analysis as a new guidance document for diagnosing and treating K. pneumonia infections is needed to raise the awareness of infectious disease specialists, gastroenterologists, and microbiologists to the heteroresistance to colistin in patients with a K. pneumonia infection.